Evaluation of the Accuracy and Practicability of Predicting Compression Garment Pressure Using Virtual Fit Technology. (April 2023) - Brubacher, Kristina; Tyler, David; Apeagyei, Phoebe; Venkatraman, Prabhuraj; Brownridge, Andrew Mark
In this study, we evaluated the feasibility of using the virtual fit pressure map in a clothing-specific CAD program to predict pressures applied by sports compression garments by analyzing pressure prediction accuracy and process practicability. In wearer trials with whole-body compression sportswear, we measured in vivo pressures and compared them to virtual pressures recorded from the virtual fit pressure maps of the garments fitted to 13 participants' body scan avatars. No clear correlations between virtual and in vivo pressures were identified and problems in the virtual fit process became apparent. The CAD software currently lacks a link to physical fabric, seam and component properties, which inhibits its use for predictions in new product development. By considering all simulation settings and assessing the numerical pressure prediction capability of a clothing-specific CAD program, this research provides a step forward in assessing the limitations of virtual fit for technical product development.